The SAGE Handbook of Personality Theory and Assessment: Volume 2 — Personality Measurement and Testing 2008
DOI: 10.4135/9781849200479.n13
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Personality Through Test Construction: Development of the Multidimensional Personality Questionnaire

Abstract: Construct explication through factor or components analysis: A review and evaluation of alternative procedures for determining the number of factors or components. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
1,016
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 726 publications
(1,047 citation statements)
references
References 0 publications
25
1,016
1
5
Order By: Relevance
“…Given that goal, it is very difficult (both conceptually and analytically) to provide a concise and cogent illustration of the consequences of suppressor situations using more than two predictor variables. 2 Although the Schmitt and Newman (1999) study included nine self-report measures, two of these measures (Harm Avoidance and Constraint) have been shown to be indicators of behavioral disinhibition rather than the emotional aspect of fear associated with NEM (Tellegen & Waller, 1992).…”
Section: Suppressor Effectsmentioning
confidence: 99%
See 4 more Smart Citations
“…Given that goal, it is very difficult (both conceptually and analytically) to provide a concise and cogent illustration of the consequences of suppressor situations using more than two predictor variables. 2 Although the Schmitt and Newman (1999) study included nine self-report measures, two of these measures (Harm Avoidance and Constraint) have been shown to be indicators of behavioral disinhibition rather than the emotional aspect of fear associated with NEM (Tellegen & Waller, 1992).…”
Section: Suppressor Effectsmentioning
confidence: 99%
“…Given that goal, it is very difficult (both conceptually and analytically) to provide a concise and cogent illustration of the consequences of suppressor situations using more than two predictor variables. 2 Although the Schmitt and Newman (1999) study included nine self-report measures, two of these measures (Harm Avoidance and Constraint) have been shown to be indicators of behavioral disinhibition rather than the emotional aspect of fear associated with NEM (Tellegen & Waller, 1992 Recently, researchers have demonstrated that suppressor effects fall within the same intervening variable framework as mediating and confounding effects, wherein the impact of an initial predictor is partitioned into a direct and an indirect effect via a third variable (MacKinnon, Krull, & Lockwood, 2000;Shrout & Bolger, 2002). In this model, suppression occurs when the indirect effect of a predictor is opposite that of its direct effect.…”
mentioning
confidence: 99%
See 3 more Smart Citations